PENGEMBANGAN PERANGKAT PEMBELAJARAN IPS BERORIENTASI MODEL PROBLEM BASED LEARNING BERBANTUAN MEDIA VIDEO UNTUK MENINGKATKAN HASIL BELAJAR SISWA KELAS IV SD - Purwanto, Anton (Universitas Negeri Surabaya, 2019)
ABSTRACTThis research aims to produce learning instrument of social science oriented model of problem based learning aided of video media and can improve student learning outcomes fourth grade of elementary school. Planning phase was aimed to develop instruments with 4-D Model by Thiagarajan (1974) which is reduced into 3-D (define, design, and develop). Action phase is learning process in the classroom using one-group pretest-posttest design. The results showed that the develop instruments fit for use because it has met the criteria of a valid, practical, and effective. Valid seen from the validity of the content of the lesson plan, student teaching materials, students worksheet, media, and learning outcome test with an average value of 3,19 has a good category, student teaching materials legibility and students worksheet respectively 82,5% had both categories, the sensitivity of items categorized as sensitive. Practical implementation of learning can be seen from the percentage of 91,04% has a very good category, the problems encountered uring the learning can be overcome. Effective learning is seen from the increased activity of students in each meeting, student responses 90,83% have a very good category. Student learning outcomes increased with N-gain average of 0,65 is considered a moderate increase. Based on the research results can be concluded that the application of the model of Problem Based Learning aided video media can improve student learning outcomes and the development of the Sosial Science oriented learning model of Problem Based Learning aided video media fit for use in the learning process because it has met the criteria of a valid, practical, and effective. Keywords: Learning Instrumen, Problem Based Learning. ABSTRAKPenelitian ini bertujuan untuk menghasilkan perangkat pembelajaran IPS berorientasi model Problem Based Learning berbantuan media video yang layak dan dapat meningkatkan hasil belajar siswa kelas IV SD. Penelitian ini dilaksanakan dalam dua tahap, yaitu tahap persiapan yang bertujuan mengembangkan perangkat mengikuti rancangan 4-D model dari Thiagarajan (1974) yang direduksi menjadi 3-D (define, design, and develop). Dilanjutkan dengan tahap pelaksanaan pembelajaran di kelas menggunakan rancangan one group pretes-posttest design. Hasil penelitian menunjukkan bahwa perangkat yang dikembangkan layak digunakan karena telah memenuhi kriteria valid, praktis, dan efektif. Valid terlihat dari validitas isi RPP, BAS, LKS, media, dan THB rata-rata 3,19 berkategori baik; keterbacaan BAS dan LKS masing-masing sebesar 82,5% berkategori baik: sensitivitas butir soal dikategorikan peka. Praktis terlihat dari persentase keterlaksanaan pembelajaran 91,04% kategori sangat baik; kendala-kendala yang ditemui selama pembelajaran dapat diatasi. Efektif terlihat dari peningkatan aktivitas siswa dalam setiap pertemuan; respon siswa 90,83% kategori sangat baik. Hasil belajar siswa meningkat dengan N-gain rata-rata 0,65 dikategorikan peningkatan sedang. Berdasarkan hasil penelitian dapat disimpulkan bahwa penerapan model Problem Based Learning berbantuan media video dapat meningkatkan hasil belajar siswa dan perangkat pembelajaran IPS berorientasi model Problem Based Learning berbantuan media video layak digunakan dalam proses pembelajaran karena telah memenuhi kriteria valid, praktis, dan efektif. Kata Kunci: Perangkat pembelajaran, Problem Based Learning.